Customer satisfaction indicators in transportation and distribution factors of online shopping company - Thanyaphat Muangpan (Cogent Business & Management, 2022)
The commercial business model has changed to electronic market channels and electronic distribution. Electronic commerce (E-commerce) and shopping online generate profits and reduce costs. Many businesses are creating new channels using digital network technology. This research explores the factors and indicators of customer satisfaction for transportation and distribution in an online shopping company. Survey research and exploratory factor analysis (EFA) is applied to analyse the data collection concerning Chinese customers in Thailand who have used the services of an online shopping company. This research tested the results for validity, reliability, and Kaiser-Meyer-Olkin (KMO) statistical approach. Factor loadings confirm the factor explanations and the common threshold of 0.7. Furthermore, customer satisfaction in transportation and the distribution management model achieves with the three main factors and fifteen key indicators. The three factors are the Responsibility of Product and delivery in transportation and distribution, customer services in transportation and distribution, and customer communication in transportation and distribution. These fifteen indicators and the information are to improve the e-commerce business model to create a competitive advantage and increase market share.
Keywords: 650; Customer satisfaction indicators; distribution; electronic commerce (e-commerce); shopping online; Transportation